Application of carboxylated carbon nanotubes in gas sensing - Kwan, Ronnie Kwok Hoong. (2010)
This project aim to increase on the sensitivity of carboxylated CNTs based devices to gases with different concentration of nitric acid used. In this project, 2 method of deposition the CNTs onto the subsrate are carried. They are the thermal Chemical Vapor Deposition method and the drop-cast method. The CNTs involved in this project are carboxylated with nitric acid at 1M, 2M and 4M. The procedures involved to carboxylate the CNTs are illustrated at the experimental procedure in this report. The receptors fabricated in this project are used as gas detecting agents for NO and CO gases in the laboratory. Gas sensing procedures are carried out using a Keithley 4200 probe station which is installed within a gas chamber in the polymer electronics laboratory at School of Materials Science and Engineering. Results have shown that the sensitivity of carboxylated CNTs varies with the concentration of nitric acid used to carboxylate the CNTs. The sensitivity towards NO gas is optimum with 2M of nitric acid. The positive result shown was tested by carboxylated CNTs that were deposited by the thermal Chemical Vapor Deposition method. It is reported by T. Ueda that temporal change rate of the resistance was proportional to the concentration of the targeted gas for multi-wall CNTs based sensors prepared by thermal Chemical Vapor Deposition method. [1] Though by varying the operating temperature is one of the ways to increase the sensitivity, the high temperature environment required makes it unrealistic for field deployment usage. In this project, the result realizes the possibility of future field deployment usage of CNTs as the sensitivity of gas sensor can be increase by varying the acid concentration to the CNTs. Future research work can be carried in this direction to develop a high performance gas receptor that is able to show high sensitivities, high stability and high selectivity that can distinguish more variety of gases.